IMPLEMENTASI ALGORITMA BARNI SYMMETRIC UNTUK WATERMARKING CITRA DIGITAL - Brian Damastu Ridho Hutama; M.Agus Sunandar (Jurnal Teknologika, 2024)
Image watermarking is a solution to protect digital images of issues such as copyright protection, ownership, authentication, fingerprinting, and etc. Digital watermarking method using a symmetric algorithm Barni on digital images with a correlation-based method in the domain of Discrete Cosine Transform (DCT). Color images in RGB color space is transformed first into the YCbCr color space. Watermark is inserted in the array f, then the results are transformed back into RGB color space. Watermark is the real line and along the N elements are normally distributed. Watermark is inserted in the selected DCT coefficients of middle frequency sub-band to get a balance between robustness and imperceptibility. Watermark detection is done by calculating the correlation between the received image with the original watermark, and then compare it with an-value threshold. The test results are binary decision stating the image contains a watermark or not contain the watermark. The experimental results show that air-quality image watermark can not be distinguished from the original image and Barni symmetric method has proven robust against some non-malicious attacks such as JPEG compression attack, histogram equalization, gamma correction, noising, sharpening